Long-term climate warming weakens positive plant biomass responses globally - Pengfei Dang; Philippe Ciais; Jiaxin Gao; Yunxiao Zhu; Jiquan Xue; Xiaoliang Qin; Gerard H. Ros (Proceedings of the National Academy of Sciences, 2025)
Carbon sequestration through plant biomass responses to global warming plays a vital role in mitigating climate change, but recent evidence suggests that this effect diminishes in the long term. To investigate the effect of warming duration on plant biomass responses, we analyzed a global dataset of 2,291 paired observations, revealing that warming increased overall aboveground plant biomass by 9.4% and belowground biomass by 2.6%. However, as the warming duration increased, the positive plant biomass response shifted to neutral or negative, with great biomass reductions in regions where mean annual temperatures exceeded 10 °C. Global aboveground biomass is projected to decline by 4 to 16% under a 2 °C increase in climate warming. Our study suggests that long-term climate warming will significantly weaken plant carbon storage, even if temperature increases remain within the targets of the Paris Agreement, and offers empirical constraints for global biomass–climate models.